Hot Money Flows, Cycles in Primary Commodity Prices, and Financial Control in Developing Countries - Ronald McKinnon (Fondation pour les études et recherches sur le développement international (FERDI), 2014)
Because the U.S. Federal Reserve's monetary policy is at the center of the world dollar standard, it has a first-order impact on global financial stability. However, except during international crises, the Fed focuses on domestic American economic indicators and generally ignores collateral damage from its monetary policies on the rest of the world.Currently, ultra-low interest rates on short-term dollar assets ignite waves of hot money into Emerging Markets (EM) with convertible currencies. When each EM central bank intervenes to prevent its individual currency from appreciating, collectively they lose monetary control, inflate, and cause an upsurge in primary commodity prices internationally. These bubbles burst when some accident at the center, such as a banking crisis, causes a return of the hot money to the United States (and to other industrial countries) as commercial banks stop lending to foreign exchange speculators. World prices of primary products then collapse. African countries with exchange controls and less convertible currencies are not so attractive to currency speculators. Thus, they are less vulnerable than EM to the ebb and flow of hot money.However, African countries are more vulnerable to cycles in primary commodity prices because food is a greater proportion of their consumption, and—being less industrialized—they are more vulnerable to fluctuations in prices of their commodity exports. Supply-side shocks, such as a crop failure anywhere in the world, can affect the price of an individual commodity. But joint fluctuations in the prices of all primary products— minerals, energy, cereals, and so on—reflect monetary conditions in the world economy as determined by the ebb and flow of hot money from the United States, and increasingly from other industrial countries with near-zero interest rates.
Keywords: 330